Grape seed extract: the first protein‐based fining agent endogenous to grapes. (2nd February 2017) - Gazzola, D.; Vincenzi, S.; Marangon, M.; Pasini, G.; Curioni, A.
Abstract: Background and Aims: There is a growing interest in finding alternative wine fining agents to replace potentially allergenic animal‐derived and plant‐derived proteins. In this context, the potential use of grape‐derived fining agents would be beneficial as they would not introduce additional, potentially allergenic products to the finished wine. In this project, grape seed flour, a by‐product of the grape oil seed industry, has been used to prepare a grape seed extract (GSE) for testing as a novel wine fining agent. Methods and Results: The fining performance of GSE was compared with that of patatin, pea proteins, polyvinylpolypyrrolidone and potassium caseinate in a white and in a rosé wine, and of ovalbumin and gelatin in a red wine. Reduction of turbidity, effect on wine colour, the concentration of phenolic substances, browning potential and wine sensory attributes were determined. Grape seed extract was effective in decreasing white wine turbidity when compared to potassium caseinate. In red wine, GSE removed some anthocyanin and proanthocyanins, while wine colour was only slightly affected. The greatest GSE effect was observed on the sensory properties of the treated wines, as it strongly reduced the vegetal notes in the rosé wine and improved the overall taste of the red wine as a result of the reduction in both acidity and astringency. Conclusions: Grape seed extract can be considered a valid allergen‐free alternative to the most common wine fining agents. Significance of the Study: Grape seed extract is the first effective fining agent endogenous to grapes, thus not attracting the legal restrictions concerning the presence of foreign substances.